STRATEGI PEMBANGUNAN PERTANIAN DAN PEREKONOMIAN PEDESAAN MELALUI KEMITRAAN USAHA BERWAWASAN PENGEMBANGAN MEKANISASI PERTANIAN DI KABUPATEN NGAWI : Strategi, Pengembangan, Pertanian, Pedesaan, Alat Mesin Pertanian - Suhardjito, Suhardjito; Hikmawati , Meiyana (innofarm, 2023)
Agricultural and rural economic development strategies through business partnerships with an insight into the development of machine tools. The purpose of writing this acuentific work ia for (1) Discusses the rural economic profile as a basic for planning development programs, (2) Discusses strategies for rural development with an agribusines perspective, and (3) Formulate policies for the development of Machinery in a comprehensive and integrative manner. The process of economic development of a nation implicitly requires the tranformation of traditional agriculture into advanced or modern agriculture. It is in the tranformation process that patterns of participation play a role. Advanced agriculture is agriculture that has the ability to continually adapt to ever changing and demands. Agribusines partnership institusions that can eliminate these various failures are integrated agribusines business institusions in the form of integration between (farmer, trader, processor) and products qualityraw materialis, excellent post Harvest handlinh and guaranteed food safety). This model is supported by the institutional revitalization of farmer groups, agricultural extension, and partner companies.